2017
DOI: 10.2147/dddt.s131670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin extended release compared to immediate release formula on glycemic control and glycemic variability in patients with type 2 diabetes

Abstract: PurposeThe purpose of this study is to evaluate, in a randomized clinical trial, the effects of metformin immediate release (IR) compared with metformin extended release (XR) on the gastrointestinal tolerability and glycemic control.Materials and methodsWe enrolled 253 Caucasian patients with type 2 diabetes not well controlled by diet (glycated hemoglobin [HbA1c] >7.0% and <8.5%). Patients were randomized to metformin IR or metformin XR for a period of 6 months at the maximum tolerated dose. The average dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 17 publications
1
37
0
2
Order By: Relevance
“…This feature helps to provide slower, smoother, and longer gastric residence time of metformin 500 mg PR tablet, without an initial rapid rise in plasma metformin (GelShield diffusion system). The results of this study were in agreement with the published literature in reporting fewer GI side effects with the use of once-daily metformin PR formulation than that of immediate-release metformin 21,22…”
Section: Discussionsupporting
confidence: 91%
“…This feature helps to provide slower, smoother, and longer gastric residence time of metformin 500 mg PR tablet, without an initial rapid rise in plasma metformin (GelShield diffusion system). The results of this study were in agreement with the published literature in reporting fewer GI side effects with the use of once-daily metformin PR formulation than that of immediate-release metformin 21,22…”
Section: Discussionsupporting
confidence: 91%
“…The extended-release form of metformin appeared to reduce weight and inflammation, with fewer side effects than the immediate-release metformin in diabetic people [ 82 ], representing a promising avenue in nondiabetic PWH. The duration and optimal metformin dosage will have to be defined before implementing a large randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized clinical trial studied the effects of metformin immediate release compared with metformin extended release on glycemic control in type 2 diabetes mellitus (T2DM) [ 118 ]. The authors observed increased levels of visfatin in patients randomized to metformin extended release [ 118 ]. Another trial showed a reduction in visfatin serum levels after metformin administration in PCOS women [ 119 ].…”
Section: Relevance Of Visfatin To Metabolic Diseasesmentioning
confidence: 99%